THE TYPES OF MODERN LINGUISTICS AND THEIR PLACE IN UZBEK LINGUISTICS - G’aniyeva, Hayriniso (Maktabgacha taʼlim jurnali, 2023)
This article discusses the current types and trends in modern linguistics.